Efektivitas Penatausahaan Keuangan di Kecamatan Johan Pahlawan Kabupaten Aceh Barat Provinsi Aceh - Bismi, Muhammad Ilham Surya; Utomo, Decky Dwi (Innovative: Journal Of Social Science Research, 2025)
Financial administration is an important part of realizing good governance, especially in terms of public financial management accountability. This study aims to analyze the effectiveness of financial administration in Johan Pahlawan District, West Aceh Regency through the use of the Local Government Information System (SIPD). The method used is qualitative with data collection techniques through observation, documentation, and literature study. The data were analyzed using W. Jack Duncan's Organizational Effectiveness Theory which includes indicators of goal achievement, integration, and adaptation. The results showed that the stages of financial administration in this sub-district have run effectively, supported by the use of SIPD which is integrated at each stage. Even so, there are still obstacles such as limited operators and network disruptions, but they are minimal and do not hamper the overall process.